2017
DOI: 10.4236/ojog.2017.711114
|View full text |Cite
|
Sign up to set email alerts
|

How Referred Patients Influence Cesarean Sections Rate Pattern: Analysis according to the Robson Classification

Abstract: Objective: To improve the practice of cesarean section by analyzing the cesarean section according to Robson's classification. Methodology: This was a cross-sectional and descriptive study carried out at the University Hospital of Cocody. It covered the Cesarean sections performed during the year 2015 and ranked according to the 10 groups of Robson. Results: The overall Cesarean section rate in 2015 was 42.8% (3100 cesarean sections for 7229 deliveries). Group 1 was the largest contributor to overall Cesarean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…A higher proportion of referred women ended up with emergency CS. The main reason is previous CS scar, aligning with findings from other studies 21,22 . As a predetermined risk, counselling during pregnancy and referral to a comprehensive EmONC facility before the onset of labour should be emphasized as a preventive aspect of risks associated with previous CS scars.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A higher proportion of referred women ended up with emergency CS. The main reason is previous CS scar, aligning with findings from other studies 21,22 . As a predetermined risk, counselling during pregnancy and referral to a comprehensive EmONC facility before the onset of labour should be emphasized as a preventive aspect of risks associated with previous CS scars.…”
Section: Discussionsupporting
confidence: 63%
“…The main reason is previous CS scar, aligning with findings from other studies. 21,22 As a predetermined risk, counselling during pregnancy and referral to a comprehensive EmONC facility before the onset of labour should be emphasized as a preventive aspect of risks associated with previous CS scars. Obstructed labour further contributed substantially to CSs in the referral group.…”
Section: Discussionmentioning
confidence: 99%
“…The caesarean section rate in Tanzania increased from 19 per cent to 49 per cent in the decade leading up to 2013. In addition, Koffi et al (2017Koffi et al ( , 1134 found that emergency caesarean section rates had increased to 69.9 per cent in the total study population of hospitals situated in the Ivory Coast. Hoxha et al (2017, 1) argue that caesarean sections are performed more often in private hospitals for profit, as compared to those in public non-profit hospitals.…”
Section: Introductionmentioning
confidence: 95%
“…The World Health Organization (WHO 2015) states that caesarean section rates should not exceed 10 per cent to 15 per cent of the entire population in a country. According to Koffi et al (2017Koffi et al ( , 1137, the caesarean section rates at hospitals in Cairo, Egypt, were between 35.2 per cent and 52.1 per cent in 2014. The caesarean section rate in Tanzania increased from 19 per cent to 49 per cent in the decade leading up to 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation